Preceptors' Views of Preceptorship: An Interpretative Phenomenological Analysis. (August 2014) - Maringer, Tracy; Jensen, Jan
Introduction: Preceptorship is a structured, supported induction period, the purpose of which is to ease the student—practitioner transition for newly qualified Band 5 National Health Service workers. The aim of this research, set in an acute hospital setting, was to explore the views of therapists on their roles as preceptors. Method: In this qualitative study, three occupational therapists and three physiotherapists participated in semi-structured interviews to identify their perceptions of the preceptor role and their thoughts on how the preceptorship programme affects preceptees' student—practitioner transitions. Interpretative phenomenological analysis identified emergent themes from the data. Findings: Three main themes emerged: valuing structured learning and reflection; the requirements of the preceptor—preceptee relationship; and the perceived impact of preceptorship on the service. Conclusion: The preceptorship programme was commended for providing a structured induction, facilitating reflective practice in newly qualified staff, and enhancing standards of clinical care for patients. It was felt that improved training in being a preceptor and ways of engaging in the process of preceptorship, along with alterations to simplify and clarify the local preceptorship programme paperwork, would benefit both preceptors and preceptees.